Influence of phosphate anions on the stability of immobilized enzymes. Effect of enzyme nature, immobilization protocol and inactivation conditions ... : تأثير أنيون الفوسفات على استقرار الإنزيمات الجامدة. تأثير طبيعة الإنزيم وبروتوكول التثبيت وظروف التعطيل ... - Jakub F. Kornecki; Diego Carballares; Roberto Morellon‐Sterling; El-Hocine Siar; Saeid Kashefi; Chafiaa Mazri; Sara Arana‐Peña; Nathália Saraiva Rios; Luciana Rocha Barros Gonçalves; Roberto Fernández‐Lafuente (OpenAlex, 2020)
A destabilizing effect at pH 7 of sodium phosphate on several lipases immobilized via interfacial activation is shown in this work. This paper investigates if this destabilizing effect is extended to other inactivation conditions, immobilization protocols or even other immobilized enzymes (ficin, trypsin, β-galactosidase, β-glucosidase, laccase, glucose oxidase and catalase). As lipases, those from Candida antarctica (A and B), Candida rugosa and Rhizomucor miehei have been used. Results confirm the very negative effect of 100 mM sodium phosphate at pH 7.0 for the stability of all studied lipases immobilized on octyl agarose, while using glutaraldehyde-support the effect is smaller (still very significant using CALA) and in some cases the effect disappeared (e.g., using CALB). The change of the pH to 5.0 or 9.0, or the addition of 1 M NaCl reduced the negative effect of the phosphate in some instances (e.g., at pH 5.0, this negative effect is only relevant for CALB). Regarding the other enzymes, only the ... : يظهر في هذا العمل تأثير مزعزع للاستقرار عند درجة الحموضة 7 لفوسفات الصوديوم على العديد من إنزيمات الليباز المثبتة عن طريق التنشيط البيني. تبحث هذه الورقة في ما إذا كان هذا التأثير المزعزع للاستقرار يمتد إلى ظروف تعطيل أخرى أو بروتوكولات تثبيت أو حتى إنزيمات ثابتة أخرى (فيسين، تريبسين، β - galactosidase، β - glucosidase، لاكاز، أوكسيديز الجلوكوز وكاتالاز). كما تم استخدام الليباز، تلك من المبيضات أنتاركتيكا (A و B)، المبيضات روجوسا و Rhizomucor miehei. تؤكد النتائج التأثير السلبي للغاية لفوسفات الصوديوم 100 مللي مولار عند درجة الحموضة 7.0 لاستقرار جميع الليبازات المدروسة المثبتة على أجاروز الأوكتيل، أثناء استخدام دعم الجلوتارالدهيد، يكون التأثير أصغر (لا يزال كبيرًا جدًا باستخدام CALA) وفي بعض الحالات يختفي التأثير (على سبيل المثال، باستخدام CALB). أدى تغيير درجة الحموضة إلى 5.0 أو 9.0، أو إضافة 1 مللي كلوريد الصوديوم إلى تقليل التأثير السلبي للفوسفات في بعض الحالات (على سبيل المثال، عند درجة الحموضة 5.0، يكون هذا التأثير السلبي مناسبًا فقط لـ CALB). فيما يتعلق بالإنزيمات الأخرى، فقط مونومير β - galactosidase ...